Labor e engenho (Universidade Estadual de Campinas, 2007)
"Diffusing science and engineering aplied to sustainable regional development, valuing the work (labor) and innovation (genius/ingenium) resulting from academic research or professional experience, highlighting productive and cultural processes that integrate water and land systems, promoting the sustainability of those processes and systems from the heritage and landscape conservation viewpoint, focusing at the local development, providing expertise on urban and rural planning, land and water management (urban-rural system), the integrated river basin management, including their water and territory resources through publishing of technical-scientific papers that aim recognize in a certain region their local values as resources for sustainable development"--Focus and Scope, viewed March 9, 2020.